2017
DOI: 10.1021/acsinfecdis.6b00088
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae Lytic Transglycosylases LtgA and LtgD Reduce Host Innate Immune Signaling through TLR2 and NOD2

Abstract: Neisseria gonorrhoeae releases anhydro peptidoglycan monomers during growth through the action of two lytic transglycosylases encoded in the N. gonorrhoeae genome, LtgA and LtgD. Because peptidoglycan and peptidoglycan components activate innate immune signaling, we hypothesized that the activity of LtgA and LtgD would influence the host responses to gonococcal infection. N. gonorrhoeae lacking LtgA and LtgD caused increased host production of inflammatory cytokines IL-1β and TNF-α. Culture supernatants from Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…The contribution of LTs to pathogenesis was recently observed in N. gonorrhoeae, B. abortus and E. tarda (Liu et al, 2012;Bao et al, 2017;Knilans et al, 2017;Ragland et al, 2017). However, the molecular mechanisms connecting LTs to pathogenesis are not well defined, especially in A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of LTs to pathogenesis was recently observed in N. gonorrhoeae, B. abortus and E. tarda (Liu et al, 2012;Bao et al, 2017;Knilans et al, 2017;Ragland et al, 2017). However, the molecular mechanisms connecting LTs to pathogenesis are not well defined, especially in A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are involved in remodeling of the PG layer and releasing PG fragments (1,6-anhydro-muropeptides), and consequently, important for cell wall integrity (Dik et al, 2017). Recently, it was shown that LTs are important for pathogenesis in Neisseria gonorrhoeae, Brucella abortus and Edwardsiella tarda (Bao et al, 2017;Knilans et al, 2017;Liu et al, 2012;Ragland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Human NOD1 senses free tripeptide and tripeptide monomer and is expressed by many different cell types in humans (33)(34)(35). Human NOD2 binds to muramyl dipeptide (MurNAc L-alanine-D-glutamate) and PG monomers with a reducing end and is expressed by a limited set of cell types, including leukocytes and epithelial cells (36)(37)(38)(39)(40). Curiously, murine NOD1 recognizes tetrapeptide monomer instead of tripeptide monomer (41).…”
Section: Pg Fragments Released By Neisseria Speciesmentioning
confidence: 99%
“…Among the PG fragments released by N. gonorrhoeae, the NOD1 agonists are the disaccharide tripeptide monomer (GlcNAc-anhydroMurNAc-L-Ala-D-Glu-meso-DAP) and the free tripeptide (L-Ala-D-Glu-meso-DAP) (11,19). NOD2 recognizes whole sacculi, PG containing MurNAc and terminating with the dipeptide (MurNAc-L-Ala-D-Glu), and monomeric PG fragments that have a free hydroxyl at the reducing end (20)(21)(22). For N. gonorrhoeae, the NOD2 agonists include large PG fragments generated by autolysis and disaccharide-dipeptide monomers (GlcNAc-anhMurNAc-L-Ala-D-Glu).…”
mentioning
confidence: 99%
“…For N. gonorrhoeae, the NOD2 agonists include large PG fragments generated by autolysis and disaccharide-dipeptide monomers (GlcNAc-anhMurNAc-L-Ala-D-Glu). A third NOD2 agonist is generated by host lysozyme acting on glycosidically linked PG dimers and thereby creating PG monomers with a reducing end (22). Previous studies have demonstrated the roles of lytic transglycosylases LtgA and LtgD in producing toxic, monomeric PG fragments, including the disaccharide tripeptide monomer (8).…”
mentioning
confidence: 99%